Kajian Pengaruh Penggunaan Semen Ekspos sebagai Finishing Dinding Interior terhadap Psikologis Pengguna Ruang - Rakandenu, I Gede Made Gani; Wardhani, Dyah Kusuma (Universitas Ciputra Surabaya, 2021)
The use of exposed cement materials as wall finishing lately is in great demand and is becoming a designtrend at the moment. Many property buildings ranging from commercial buildings such as cafes, restaurants,to hotels to residential buildings such as houses, apartments and condos use exposed cement as one ofthe interior wall finishing. Exposed cement as wall finishing is usually associated with industrial designstyles. In Indonesia, exposed cement is applied as finishing material after bricks. Using exposed cementas wall finish that nowadays has been trending in architecture and interior applicants gives a differentambience of space, home or building yet still economically acceptable. The using of exposed cement aswall finish are close to the using of industrial style. As known, industrial style is an interior architecturedesign style that adopting industries elements such as the using of metal, bricks and pipe material thenbe exposed on purpose. Industrial style has color palette such as black and greyish. Therefore the usingof exposed cement as wall finish often used in industrial design style. However with the popular use ofexposed cement as wall finish does not mean that it can freely acceptable in all situations, because it canaffect the comfort of the room user.